(untitled) (MAUSAM, 1966)
Frequency distribution of times of commencement of geomagnetic disturbances at Alibag is studied. Hourly distribution of SSC (Storm Sudden Commencement) occurrences does not show any significant diurnal variation, however, a broad tendency for the frequency to be slightly higher during the day than the night is noticed. Hourly distribution of GC’s (Gradual Commencements) show 8, definite preference for the hours 6 to 12 local time, with 50 per cent occurring during that interval. Monthly distribution of both SSC and GO occurrences show a slightly higher frequency for the equinoxial months.